2004
DOI: 10.1023/b:mole.0000031459.14448.af
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of filamentous phage peptide libraries in mice

Abstract: In vivo phage display is a new approach to acquire peptide molecules that bind stably to a given target. Phage peptide display libraries have been selected in mice and humans and numerous vasculature-targeting peptides have been reported. However, in vivo phage display has not typically produced molecules that extravasate to target specific organ or tumor antigens. Phage selections in animals have been performed for very short times without optimization for biodistribution or clearance rates to a particular or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 51 publications
6
80
0
3
Order By: Relevance
“…This suggests that linear C-terminal peptides as a group may be difficult to adapt as therapeutic ligands, particularly if present as multiple copies. Whether N-terminal peptides displayed on filamentous phage are subject to similar limitations remains to be determined (Zou et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that linear C-terminal peptides as a group may be difficult to adapt as therapeutic ligands, particularly if present as multiple copies. Whether N-terminal peptides displayed on filamentous phage are subject to similar limitations remains to be determined (Zou et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As noted already in the pioneer study by Pasqualini et al, a substantial portion of injected peptide library displayed on phage fd-tet is nonspecifically sequestered by liver, which strongly interferes with selection of liver-specific peptides (Pasqualini and Ruoslahti 1996). A detailed study of phage clearance has shown that the commonly used display library FUSE5, containing random peptides at the N-terminus of the phage fd-tet protein pIII, disappears from the bloodstream of mice or loses its infectivity within 30 min after injection (Zou et al 2004).…”
mentioning
confidence: 99%
“…Furthermore, in vivo homing has also been applied to human subjects (Arap et al 2002;Krag et al 2006). To refine in vivo homing protocols, a thorough biodistribution study with immunodeficient mice was performed, and circulation time was found to be a critical variable, depending on the organ or tissue being targeted (Zou et al 2004). …”
Section: Selections In Living Organismsmentioning
confidence: 99%
“…This application of the technology is early in development and will be interesting to follow to fruition. It is important to note here that the biodistribution and clearance properties of phage-displayed peptide libraries is dependent on the target organ, strains of mice and types of phage [77] and that researchers may need to try varying in vivo screening parameters to achieve success.…”
Section: Potential Target-specific Peptides Identified Using Phage-dimentioning
confidence: 99%